2018
DOI: 10.1590/fst.25816
|View full text |Cite
|
Sign up to set email alerts
|

Quality and antioxidant potential of byproducts from refining of fruit pulp

Abstract: The potential use of byproducts from fruit processing has been evaluated in order to propose new uses as well as reducing costs and environmental impact. Most of the studies are focused on byproducts from primary transformation. However, byproducts from secondary transformation can reserve similar reuse opportunities. The aim of this study was to characterize chemical composition and antioxidant capacity that remained on byproducts from fruit processing at the pulp refinement stage. The byproducts from pulp re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In the same line of research, Dorta et al [40] assessed the effects of EtOH, water, and acetone as solvents and different temperatures on the extraction of antioxidants from mango peel and seeds. Table 1 contains some studies [15,28,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] regarding the extraction of bioactive compounds from fruit seeds and the bioactivity already studied. It is clear that new studies regarding fruit seeds should be focused on the optimization of extraction conditions and on the extraction techniques so that new value-added extracts can be potentially used as ingredients by pharmaceutical and food sectors.…”
Section: Introductionmentioning
confidence: 99%
“…In the same line of research, Dorta et al [40] assessed the effects of EtOH, water, and acetone as solvents and different temperatures on the extraction of antioxidants from mango peel and seeds. Table 1 contains some studies [15,28,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] regarding the extraction of bioactive compounds from fruit seeds and the bioactivity already studied. It is clear that new studies regarding fruit seeds should be focused on the optimization of extraction conditions and on the extraction techniques so that new value-added extracts can be potentially used as ingredients by pharmaceutical and food sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding S. mombin by-product phenolic compounds, Amariz et al [ 31 ] found a high polyphenols content (above 500 mg EAG.100 g −1 ) and antioxidant activity. Although there is a need for further studies regarding the profile of these phenolic compounds and a possible microbial activity in the S. mombin pulp and by-product, the fermentability assay of the present study showed that the presence of these ingredients in brewer’s wort represents limitations for the L. paracasei F19 fermentation and growth.…”
Section: Resultsmentioning
confidence: 99%
“…Amariz et al [64] addressed the total carotenoids content in by-products of fruit processing at the pulp refining stage. Among the fruits involved their research, it is worth highlighting the Amazonian fruits, taperebá and cupuaçu, which had a total carotenoid content of 7.000 ± 4 µg 100 g −1 and 620 ± 0.7 µg 100 g −1 , respectively [64].…”
Section: Research Using Parts Of Rich-carotenoids Fruitsmentioning
confidence: 99%